2003
DOI: 10.1103/physrevlett.90.218103
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Stochastic Resonance within the Human Brain

Abstract: We provide the first evidence that stochastic resonance within the human brain can enhance behavioral responses to weak sensory inputs. We asked subjects to adjust handgrip force to a slowly changing, subthreshold gray level signal presented to their right eye. Behavioral responses were optimized by presenting randomly changing gray levels separately to the left eye. The results indicate that observed behavioral stochastic resonance was mediated by neural activity within the human brain where the information f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
124
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(132 citation statements)
references
References 26 publications
7
124
0
1
Order By: Relevance
“…Under a small change of the solar power irradiating the earth, he proposed that an ice age transition can occur with the help of the environmental noise of the earth. Many SR phenomena have been reported for biological applications [18] such as the small signal detection of crayfish [19], information gain in ion channels [20], signal processing in the human brain [21] and so forth.…”
Section: Introductionmentioning
confidence: 99%
“…Under a small change of the solar power irradiating the earth, he proposed that an ice age transition can occur with the help of the environmental noise of the earth. Many SR phenomena have been reported for biological applications [18] such as the small signal detection of crayfish [19], information gain in ion channels [20], signal processing in the human brain [21] and so forth.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have suggested that the higher central nervous system might utilize the noise to enhance sensory information [13]. SR studies in humans can be divided in unimodal SR (signal and noise enter the same sense) [18,19], central SR (signal and noise enters in similar local receptors and later mix in the cortex) [20] and behavioral SR (similar to central SR but its effect is observed in one sense and then enacted in the behavior of the subjects) [21]. Before the SR principle was proposed, Harper [22] discovered what we currently would call crossmodal stochastic resonance while studying the effect of auditory white noise on sensitivity to visual flicker.…”
Section: Stochastic Resonancementioning
confidence: 99%
“…In humans, the visual cortex is activated by external dynamic white noise, with electrophysiological cortical responses that are independent from stimulus contrast (Fig. 1), and perception reflects signal/noise interaction and SR phenomena [70][71][72][73][74]. In a neuromagnetic study on humans, the brain responses to visual stimuli featuring a "threshold-SR" function reproduced the stimulus function both in the activated cortical structures dedicated to vision and in those devoted to language processing [74].…”
Section: Noise Stochastic Resonance and Neuronal Functionmentioning
confidence: 99%